2017
DOI: 10.1093/bmb/ldw057
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of health care services by migrants in Europe—a systematic literature review

Abstract: A comprehensive comparison across European countries is impossible because the number of studies is still limited. Further research should also help to identify barriers regarding the utilization of health care services by migrants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
118
2
9

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 146 publications
(158 citation statements)
references
References 43 publications
9
118
2
9
Order By: Relevance
“…In the present study, the system‐defined non‐urgent GED use observed among low‐acculturated women might be interpreted as inappropriate GED use due to a lack of knowledge about outpatient alternatives for gynecologic care. A systematic review of utilization of healthcare services by Graetz et al . found that, although ED use was higher, outpatient visits for specialized care were less frequent among migrants in Europe.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, the system‐defined non‐urgent GED use observed among low‐acculturated women might be interpreted as inappropriate GED use due to a lack of knowledge about outpatient alternatives for gynecologic care. A systematic review of utilization of healthcare services by Graetz et al . found that, although ED use was higher, outpatient visits for specialized care were less frequent among migrants in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Migrants are a vulnerable population with lower average levels of health and increased disease prevalence . They routinely face organizational and individual barriers to healthcare services …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations